Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To solve the equation [tex]\( \frac{x}{7} + \frac{2}{x-2} = \frac{x}{x-2} \)[/tex] for [tex]\( x \)[/tex], let's follow the steps and check for valid solutions.
First, observe the given equation:
[tex]\[ \frac{x}{7} + \frac{2}{x-2} = \frac{x}{x-2} \][/tex]
The first step is to combine the terms on the left-hand side into a single fraction:
[tex]\[ \frac{x}{7} + \frac{2}{x-2} \][/tex]
Next, we find a common denominator for the fractions [tex]\(\frac{x}{7}\)[/tex] and [tex]\(\frac{2}{x-2}\)[/tex]. The common denominator is [tex]\(7(x-2)\)[/tex]:
[tex]\[ \frac{x(x-2)}{7(x-2)} + \frac{2 \cdot 7}{7(x-2)} = \frac{x}{x-2} \][/tex]
Combine the fractions:
[tex]\[ \frac{x(x-2) + 14}{7(x-2)} = \frac{x}{x-2} \][/tex]
Now we have:
[tex]\[ \frac{x^2 - 2x + 14}{7(x-2)} = \frac{x}{x-2} \][/tex]
To clear the denominators, we multiply both sides of the equation by [tex]\(7(x-2)\)[/tex] (note that [tex]\(x \neq 2\)[/tex] to avoid division by zero):
[tex]\[ x^2 - 2x + 14 = 7x \][/tex]
Rearrange the equation to set it to zero:
[tex]\[ x^2 - 2x + 14 - 7x = 0 \][/tex]
[tex]\[ x^2 - 9x + 14 = 0 \][/tex]
Next, we solve the quadratic equation [tex]\(x^2 - 9x + 14 = 0\)[/tex] using the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = -9\)[/tex], and [tex]\(c = 14\)[/tex]:
[tex]\[ x = \frac{-(-9) \pm \sqrt{(-9)^2 - 4(1)(14)}}{2(1)} \][/tex]
[tex]\[ x = \frac{9 \pm \sqrt{81 - 56}}{2} \][/tex]
[tex]\[ x = \frac{9 \pm \sqrt{25}}{2} \][/tex]
[tex]\[ x = \frac{9 \pm 5}{2} \][/tex]
This gives us two potential solutions:
[tex]\[ x = \frac{9 + 5}{2} = 7 \][/tex]
[tex]\[ x = \frac{9 - 5}{2} = 2 \][/tex]
However, we must check for any extraneous solutions by substituting back into the original equation. Recall that [tex]\(x = 2\)[/tex] will make the original equation undefined since it involves division by zero.
Therefore, [tex]\(x = 2\)[/tex] is not a valid solution. So the only valid solution is:
[tex]\[ x = 7 \][/tex]
Thus, the correct answer is:
C. [tex]\( x = 7 \)[/tex]
First, observe the given equation:
[tex]\[ \frac{x}{7} + \frac{2}{x-2} = \frac{x}{x-2} \][/tex]
The first step is to combine the terms on the left-hand side into a single fraction:
[tex]\[ \frac{x}{7} + \frac{2}{x-2} \][/tex]
Next, we find a common denominator for the fractions [tex]\(\frac{x}{7}\)[/tex] and [tex]\(\frac{2}{x-2}\)[/tex]. The common denominator is [tex]\(7(x-2)\)[/tex]:
[tex]\[ \frac{x(x-2)}{7(x-2)} + \frac{2 \cdot 7}{7(x-2)} = \frac{x}{x-2} \][/tex]
Combine the fractions:
[tex]\[ \frac{x(x-2) + 14}{7(x-2)} = \frac{x}{x-2} \][/tex]
Now we have:
[tex]\[ \frac{x^2 - 2x + 14}{7(x-2)} = \frac{x}{x-2} \][/tex]
To clear the denominators, we multiply both sides of the equation by [tex]\(7(x-2)\)[/tex] (note that [tex]\(x \neq 2\)[/tex] to avoid division by zero):
[tex]\[ x^2 - 2x + 14 = 7x \][/tex]
Rearrange the equation to set it to zero:
[tex]\[ x^2 - 2x + 14 - 7x = 0 \][/tex]
[tex]\[ x^2 - 9x + 14 = 0 \][/tex]
Next, we solve the quadratic equation [tex]\(x^2 - 9x + 14 = 0\)[/tex] using the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = -9\)[/tex], and [tex]\(c = 14\)[/tex]:
[tex]\[ x = \frac{-(-9) \pm \sqrt{(-9)^2 - 4(1)(14)}}{2(1)} \][/tex]
[tex]\[ x = \frac{9 \pm \sqrt{81 - 56}}{2} \][/tex]
[tex]\[ x = \frac{9 \pm \sqrt{25}}{2} \][/tex]
[tex]\[ x = \frac{9 \pm 5}{2} \][/tex]
This gives us two potential solutions:
[tex]\[ x = \frac{9 + 5}{2} = 7 \][/tex]
[tex]\[ x = \frac{9 - 5}{2} = 2 \][/tex]
However, we must check for any extraneous solutions by substituting back into the original equation. Recall that [tex]\(x = 2\)[/tex] will make the original equation undefined since it involves division by zero.
Therefore, [tex]\(x = 2\)[/tex] is not a valid solution. So the only valid solution is:
[tex]\[ x = 7 \][/tex]
Thus, the correct answer is:
C. [tex]\( x = 7 \)[/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.